2019
DOI: 10.1007/s00701-019-03915-3
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory-reserve-weighted intracranial pressure versus intracranial pressure for outcome association in adult traumatic brain injury: a CENTER-TBI validation study

Abstract: Background Compensatory-reserve-weighted intracranial pressure (wICP) has recently been suggested as a supplementary measure of intracranial pressure (ICP) in adult traumatic brain injury (TBI), with a single-center study suggesting an association with mortality at 6 months. No multi-center studies exist to validate this relationship. The goal was to compare wICP to ICP for association with outcome in a multi-center TBI cohort. Methods Using the Collaborative European N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“… Area under RAP over time: Given complexities with interpreting RAP, we determined the area under the RAP over time curve for the RAP thresholds of 0 and + 0.4 (RAP AUC 0, and RAP AUC + 0.4), using a linear interpolation method of integration. Such methodology has been described previously by our group [ 34 , 35 ]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… Area under RAP over time: Given complexities with interpreting RAP, we determined the area under the RAP over time curve for the RAP thresholds of 0 and + 0.4 (RAP AUC 0, and RAP AUC + 0.4), using a linear interpolation method of integration. Such methodology has been described previously by our group [ 34 , 35 ]. …”
Section: Methodsmentioning
confidence: 99%
“…Data from such preliminary work supports the association between persistently elevated ICP and mortality at 6 months post-TBI. [ 6 , 14 , 24 ] Similarly, persistent ICP elevations have been shown to be potentially linked to lower CPP values, [ 6 ] worse compensatory reserve, [ 5 , 34 ] impaired cerebrovascular reactivity, [ 1 , 10 , 14 ] lower PbtO 2 values, [ 16 , 22 ] and autonomic dysfunction, [ 15 , 26 ] in those rare data sets with high-frequency digital physiology. However, most studies have suffered from several limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, continuously assessed cerebral compensatory reserve using the RAP index (correlation [R] between pulse amplitude of ICP [A] and ICP [P]), 23 has been linked to CT evidence of diffuse intracranial injury 7 and 6-month global outcomes in TBI populations. 24,25 Currently, our understanding of the impact of guideline-based therapeutics, including the effects of sedatives and vasopressors, is limited to a small number of studies using aggregate data. 10,13,26,27 A recent 25year retrospective analysis by Donnelly and associates suggested that, despite changes in TBI management guidelines over various epochs, cerebrovascular reactivity remained essentially unchanged, with mortality rates in patients with moderate/severe TBI being relatively fixed.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, continuously assessed cerebral compensatory reserve, using the RAP (correlation (R) between pulse amplitude of ICP (A) and ICP (P)), has emerged as a potential surrogate metric for compliance [ 11 , 31 , 49 , 50 ]. Recent data suggests association of high area under the RAP vs. time curve, with admission CT characteristics of diffuse intracranial injury, as well as poor global outcome at 6 months post-TBI [ 50 ].…”
Section: Introductionmentioning
confidence: 99%